Rheological behavior of polymer-based drilling fluids: experimental study of temperature effects - Safi, Brahim; Aboutaleb, Djamila; Haider, Soumya (Zielona Góra: Uniwersytet Zielonogórski)
Drilling fluids most commonly used are generally based on polymers. Polymers such as methylcellulose carboxylate (CMC), polyanionic cellulose (PAC) and xanthan (Xn) have a very important role in the success of drilling operations. Indeed, they are also used to improve certain properties, in particular rheological. However, these polymers can lose their characteristics under the influence of increasing temperature at the bottom of oil wells, thus affecting the ability of the mud to perform its useful role in the drilling operation, namely to raise the cuttings from the bottom of the well to the surface.
Keywords: polymers; methylcellulose carboxylate; drilling fluid; shear stress; viscosity; rheological behavior